PENGARUH PUCUK DAUN KACANG PANJANG (VIGNA SINENSIS) TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU POSTPARTUM KLINIK ALISAH TREISYA DI KOTA MEDAN TAHUN 2022 - Mutiara Dwi Yanti; VITRILINA HUTABARAT; dosma sinta roha; septa dwi insani (JURNAL ILMIAH DHDT - KEBIDANAN, 2022)
insufficient breast milk production is the primary cause why mothers cease breastfeeding early. The content of cypinone and polyphenol compounds within the leaves of lengthy beans (Vigna Sinensis L) has a lactation effect, so it can growth breast milk secretion and stimulate breast milk. This examine aimed to reveal the impact of feeding babies with long-leaf bean sprouts on growing lactation in postpartum mothers. This form of take a look at is a semi-experimental examine with a pre-test and publish-check group. A sample of 16 postpartum mothers who met the inclusion and exclusion criteria received postnatal mothers up to 250 g for 7 days. The device used become a survey. This observe was conducted the use of Wilcoxon's take a look at, and it changed into discovered that contributors who have been fed lengthy bean sprouts have been capable of growth their milk production by using 75%, which is sufficient for a 25% boom. The results of the analysis reached p 0.000 (p £ 0.05) indicating an increase in postnatal breast milk manufacturing. it could be concluded that the leaves of fenugreek which might be saved for a long term can increase lactation in postpartum mothers.